Impact of acute kidney injury on coagulation in adult minimal change nephropathy. Issue 46 (November 2016) - Huang, Meng-Jie; Wei, Ri-bao; Su, Ting-yu; Wang, Yang; Li, Qing-ping; Yang, Xi; Lv, Xiao-meng; Chen, Xiang-mei
Abstract : Abstract: A hypercoagulable state exists in patients with nephrotic syndrome (NS), which more easily leads to venous thromboembolism (VTE). However, whether acute kidney injury (AKI), a common complication of NS, affects the hypercoagulable state and VTE has rarely been elucidated. In this study, we aimed to explore coagulation changes and analyze relevant influencing factors in NS-AKI patients. A total of 269 consecutive NS patients with minimal change disease (MCD) between 2011 and 2016 were included in this observational study. Ninety-one cases were in the AKI group and 178 cases in the non-AKI group. The 1:1 propensity score matching (PSM) method was applied to match the baseline information. The coagulation biomarkers were compared, and the thrombosis events were recorded. Linear correlation was performed to detect any relation between D-dimer and clinical data. The PSM method gave matched pairs of 88 MCD patients with AKI and non-AKI patients, resulting in no differences in baseline information. The D-dimer, fibrinogen, and thromboelastography parameters maximum amplitude (MA), G values of the MCD-AKI patients were significantly higher than the levels of the MCD patients without AKI (D-dimer: 1.8 [1.0, 3.3] vs 1.1 [0.6, 1.7] mg/L, P < 0.001; fibrinogen: 7.0±2.0 vs 6.5 ± 1.4 g/L, P = 0.036; MA: 74.6 ± 5.0 vs 70.5 ± 5.3 mm, P = 0.020; G: 15.7 ± 5.3 vs 12.5 ± 3.3, P = 0.034). For the MCD patients, the serum creatinine, white blood cell count, and interleukin-6 levels in the patients with D-dimers >1 mg/L were significantly higher than those of patients with D-dimers ≤1 mg/L. The correlation analysis showed that the D-dimer level was correlated with serum creatinine, white blood cell count, and interleukin-6 ( r = 0.410, P = < 0.001; r = 0.248, P = < 0.001; r = 0.306, P = < 0.001, respectively). Five deep vein thrombosis events occurred in the AKI group and 1 pulmonary embolism event occurred in the non-AKI group after adjusting the propensity score value. AKI appeared to have an association with higher incidence of VTE, but the difference was not statistically significant (RR: 4.9, 95% CI: 0.6–42.7, P = 0.154). The MCD-NS patients complicated with AKI had a more severe hypercoagulable state, which might be associated with the active inflammation of AKI that mediated activation of the coagulation system.